Two cases of measles after vaccination with measles mumps and rubella combined live attenuated vaccine - SHEN Jinhua; HU Tajing; CHEN Wenhua; QIAN Jingxian; LU Hongmei (Shanghai yufang yixue, 2022)
Measles is an acute respiratory infectious disease caused by the measles virus. It is highly infectious and easy to occur in children. It causes many serious complications such as tracheitis， otitis media and pneumonia. Since the promotion of the measles vaccine in China， the measles epidemic has been effectively controlled. From June 1， 2020， the immunization procedure of measles-containing vaccine for children in Shanghai has been adjusted to one dose of measles， mumps and rubella combined live attenuated vaccine （MMR） at the age of 8 months， 18 months and 6 years. There is generally no local reaction after the injection of the MMR vaccine. A few individuals may have transient fever and scattered rash， which generally fade away by themselves. However， because it is a live vaccine， it may cause vaccine related diseases in extremely rare cases. This paper reports two cases of measles after vaccination with the MMR vaccine.